(untitled) (Research, Society and Development, 2024)
Puerperal infection (PI) is classified as the occurrence of a bacterial infection of the female genital tract. It can occur from the moment the membranes rupture, during labor or even up to the 42nd day postpartum. It is estimated that 10% of maternal deaths worldwide are caused by PI. In view of the above, the aim of this study is to identify the main risk factors for puerperal infection and the importance of humanized nursing care in order to avoid such situations. The integrative review model was chosen for the design and purpose of the study since this method can enable the identification of previous research and support positive information in the research. In order to prepare the research, a data search was carried out in the December 2023 interval, through the databases, then, after the search strategy for the articles, there was an objective and descriptive evaluation to identify the studies for the composition of the review article. Given this search and choice of studies, the research has 07 studies. This study made it possible to correlate data from Brazil and other countries regarding the identification of risk factors and the importance of humanized assistance involving the care provided by nurses to help reduce the risks of puerperal infection. The nursing team has the main role in preventing and caring for any and all signs of puerperal complications involving the parturient, as it is the professional who has the longest contact with the patient and can therefore identify and act early in the treatment. In this way, the study allowed for the necessary and pertinent immersion in a topic that is part of obstetric reality, contributing to future research on the subject.